Exploiting collateral sensitivity in the evolution of resistance to tyrosine kinase inhibitors in soft tissue sarcomas - Mark L. Elms; Andrew D. Jenks; Avirup Chowdhury; Lukas Krasny; Madhumeeta Chadha; Kaan Low; Peter T. Harrison; William G. Kerrison; Robin L. Jones; Paul H. Huang (Communications Biology)
Abstract Broad-spectrum multi-target tyrosine kinase inhibitors (mTKIs) are clinically approved for the treatment of soft tissue sarcomas (STS). However, acquired resistance inevitably arises in the majority of STS patients. There is therefore an urgent need to identify new strategies to overcome resistance and achieve durable treatment responses. Here we show that STS cells that acquire resistance to clinically relevant mTKIs are cross-resistant to one another and sequential treatment does not delay the acquisition of drug resistance. Instead, we find that en route to acquiring drug resistance, STS cells develop collateral sensitivities to alternative drugs. We demonstrate that the mTKI sitravatinib rapidly induces collateral sensitivity to the FGFR inhibitor infigratinib which can be exploited for adaptive therapy to suppress STS cell growth. This study provides proof-of-principle that collateral sensitivity may be an effective strategy for overcoming resistance to mTKIs and this novel approach should be explored in the design of future trials.